A STUDY OF CORPORATE GOVERNANCE STRUCTURE, DISCLOSURE AND INFORMATION ASYMMETRY IN INDONESIA BANKING INDUSTRY - Sihombing, Jenny; Pangaribuan, Hisar (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2017)
The purposes of this study are to find out the effect of corporate governance structure on information asymmetry, to find out the effect of corporate governance structure on disclosure, and to find out the effect of disclosure on information asymmetry in Indonesia banking industry. This study used partial least square/ variance based statistical method. Ã‚Â The results of this study found out that good implementation of corporate governance structure will increase disclosure in Indonesia banking industry. The other result implied that the higher implementation disclosure will reduce information asymmetry in Indonesia banking industry (disclosure represented by the indicator of percentage corporate governance items disclosed or as IPCG).